A Quantitative Analysis of OnabotulinumtoxinA, AbobotulinumtoxinA, and IncobotulinumtoxinA: A Randomized, Double-Blind, Prospective Clinical Trial of Comparative Dynamic Strain Reduction. Issue 5 (May 2016) - Wilson, Anthony J.; Chang, Brian; Taglienti, Anthony J.; Chin, Bianca C.; Chang, Catherine S.; Folsom, Nancy; Percec, Ivona
Abstract : Background: U.S. Food and Drug Administration–approved formulations of botulinum toxin include onabotulinumtoxinA (Botox; Allergan, Inc., Irvine, Calif.), abobotulinumtoxinA (Dysport; Galderma Pharma S.A., Lausanne, Switzerland), and incobotulinumtoxinA (Xeomin; Merz Pharmaceuticals GmbH, Frankfurt am Main, Germany). This study uses digital image correlation to compare dynamic strain reduction between available neurotoxins. Methods: Seventy-three treatment-naive female patients aged were randomized to injection with onabotulinumtoxinA (20 units), abobotulinumtoxinA (60 units), or incobotulinumtoxinA (20 units) in the glabella. Imaging was conducted at 4, 14, and 90 days after injection. Change in average dynamic strain of the glabella was compared using ANOVA. Results: At day 4, there was a 42.1 percent strain reduction in the onabotulinumtoxinA group, a 39.4 percent strain reduction in the abobotulinumtoxinA group, and a 19.8 percent strain reduction in the incobotulinumtoxinA group (onabotulinumtoxinA versus abobotulinumtoxinA, p = 0.77; onabotulinumtoxinA versus incobotulinumtoxinA, p = 0.02; and abobotulinumtoxinA versus incobotulinumtoxinA, p = 0.04). At day 14, there was a 66.1 percent strain reduction in the onabotulinumtoxinA group, a 51.4 percent strain reduction in the abobotulinumtoxinA group, and a 42.8 percent strain reduction in the incobotulinumtoxinA group (onabotulinumtoxinA versus abobotulinumtoxinA, p = 0.14; onabotulinumtoxinA versus incobotulinumtoxinA, p = 0.02; and abobotulinumtoxinA versus incobotulinumtoxinA, p = 0.36). At day 90, there was a 43.5 percent strain reduction in the onabotulinumtoxinA group, a 38.4 percent strain reduction in the abobotulinumtoxinA group, and a 25.3 percent strain reduction in the incobotulinumtoxinA group (onabotulinumtoxinA versus abobotulinumtoxinA, p = 0.66; onabotulinumtoxinA versus incobotulinumtoxinA, p = 0.12; and abobotulinumtoxinA versus incobotulinumtoxinA, p = 0.24). Conclusions: Using digital image correlation, the tested neuromodulators do not have equivalent strain reduction in the glabella at the doses used. These results confirm assertions of noninterchangeability. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, II.